Controlling Cr3+/Cr4+ concentration in single-phase host toward tailored super-broad near-infrared luminescence for multifunctional applications. (December 2021) - Cai, H.; Chen, H.; Zhou, H.; Zhao, J.; Song, Z.; Liu, Q.L.
Abstract: Full control on the valence of the active ions in solids to improve properties is the central topic of chemistry and materials. Cr 3+ and Cr 4+ ions generally emit wavelength-different near-infrared (NIR) light. Here, we have developed a chromium valence-controllable single-phase phosphor, Mg2 GeO4 :Cr 3+, Cr 4+ to achieve super-broad NIR luminescence. High Li  +  content charge compensators can stabilize Cr 3+, whereas high-temperature sintering tends to facilitate the formation of Cr 4+ . Through fine adjusting the synthesis conditions, pure Cr 3+ or Cr 4+ luminescence can be obtained with peak emission locating at 935 nm and 1190 nm, respectively. Super broad band dual emission spanning from 650 nm to 1600 nm is realized via fully controlling the concentration ratio of Cr 3+ to Cr 4+ in a single host. By measuring the transmission spectra of several foodstuff illuminated by our phosphors, non-destructive analysis in food safety areas can be realized. This study provides a new strategy for exploiting super broad band NIR luminescent materials. Highlights: The transformation of Cr 3+ to Cr 4+ or a mix valence can be feasibly tuned in Mg2 GeO4 . Near-infrared emission can be adjusted by controlling the ratio of Cr 3+ to Cr 4+ . Super broad luminescence can meet various applications, for example, non-destructive analysis.